Uji Aktivitas Antibakteri Ekstrak Kulit Batang Dadap Serep (Erythrina Subumbrans) Terhadap Bakteri Shigella Boydii dan Vibrio Cholerae - Sakdiyah, Solehatun (Universitas Harapan Bangsa, 2025)
Dadap serep (Erythrina subumbrans) has been traditionally used to relieve stomach pain. This study aimed to evaluate the antibacterial activity of dadap serep bark extract against Shigella boydii and Vibrio cholerae. The bark was extracted using the Soxhlet method, followed by phytochemical screening and antibacterial testing through the well diffusion method with three replications and a 6 mm well diameter. Mueller Hinton Agar served as the medium, while the inoculum was standardized using McFarland 0,5 and incubated for 24 hours. The extract was tested at concentrations of 100, 200, 300, 400, 500, and 600 mg/mL. Dimethyl sulfoxide (DMSO) acted as the negative control, and ceftriaxone as the positive control. Results showed that the bark extract exhibited antibacterial activity, with the largest inhibition zones observed at a 20 mg/mL concentration, measuring 6,18 mm against Shigella boydii and 6,33 mm against Vibrio cholerae. The Kruskal–Wallis test yielded p-values of 0,004 and 0,005 for Shigella boydii and Vibrio cholerae, respectively, indicating significant differences among treatment groups. The Mann–Whitney test produced p-values of 0,046 and 0,034, confirming significant differences between the 200 mg/mL concentration and the positive control. Overall, dadap serep bark extract demonstrated moderate yet effective antibacterial activity.